The Jewish enemy : Nazi propaganda during World War II and the Holocaust - Herf, Jeffrey 1947- (Belknap Press of Harvard Univ. Press, 2006)
1. The Jews, the war, and the Holocaust -- 2. Building the anti-Semitic consensus -- 3. "International Jewry" and the origins of World War II -- 4. At war against the alliance of bolshevism and plutocracy -- 5. Propaganda in the shadow of the death camps -- 6. "The Jews are guilty of everything" -- 7. "Victory or extermination" -- Conclusion